Playing with financial fire: A South perspective on the international financial system - Andrew J. Cornford (South Centre, 2018)
Playing with Fire (PWF) is a continuation of the analysis of the integration of Emerging and Developing Economies (EDEs) into the international financial system which Yılmaz Akyüz has carried out in his roles as senior economist for many years responsible for UNCTAD's Trade and Development Report and Chief Economist at the South Centre. The treatment covers cross-border financial flows, increased commercial presence of foreign financial institutions in EDEs and their increased participation in their local financial markets as well as policy and regulatory issues. PWF deploys data on major cross-border financial flows on a gross as well as a net basis. This innovative approach facilitates identification of financial stability issues posed by the increased participation of EDEs in international financial markets. The reflections which follow do not cover all the subjects raised in PWF's wide-ranging analysis. They concentrate on the discussion of the overall context of financial integration of EDEs, the progress of this integration, the continuing exposures to financial instability, and PWF's conclusions regarding policy and regulation. These policy conclusions are linked to the discussion of changes in financing linked to the liberalisation and progressive opening-up of EDEs' financial markets to non-residents. Of special importance here are continuing vulnerabilities to credit and foreign exchange risk. These have been modified by the changing distribution of the parties exposed to the risks and of the instruments which give rise to them. There is also brief discussion of the current regulatory agenda for banks. Despite the changes in the character and incidence of credit and foreign exchange risk the prudential regulation of banks' exposure to foreign exchange risk remains an important part of the picture and arguably merits more extended attention than it receives in PWF.
Keywords: 300; Finanzkrise; Internationale Staatsschulden; Wechselkurspolitik; Kreditrisiko; Währungsrisiko; Entwicklungsländer; Welt